Estudio de 8 clones extranjeros de caña de azucar (Saccharum spp. hibrido) en ciclos de 12 meses - Del Toro Martinez, F.=700 1 Martin Fagundo, D.; Saucedo Castillo, O.; Orquin Lena, J.; Gonzalez Jarquin, S.
(En, Es)
ilus., 5 ref.
Keywords: CAÑA DE AZUCAR; CLONES; CICLO VITAL; CUBA